DIFFICULTIES STUDENTS FACE WHEN LEARNING ENGLISH (Ustozlar uchun, 2026)
This article analyzes the main problems students encounter while learning English. Actually, it highlights issues such as limited vocabulary, complexities in grasping grammatical rules, and a lack of confidence in developing listening and speaking skills. Furthermore, the lack of comprehensive practical experience and psychological factors - most notably the fear of making mistakes - are examined as significant barriers. The article also proposes effective methods to overcome these obstacles. Ultimately, it emphasizes that through consistent practice and the right approach, successful English language acquisition is achievable.